Spatial and temporal variations of trophic state conditions of Lake Bunyonyi, south‑western Uganda - Saturday, Alex; Lyimo, Thomas J.; Machiwa, John; Pamba, Siajali (Applied Water Science, 2023)
The study was conducted to assess the spatial and temporal variations of the trophic state condition of Lake Bunyonyi between October 2019 and September 2020. Secchi depth (SD), total phosphorus (TP) and chlorophyll-a (Chl-a) concentration were measured to aid the quantification of trophic state condition of the lake using Carlson trophic state index (CTSI). The trophic state index (TSI) values based on SD, TP and Chl-a values were 60.82 ± 5.35, 68.99 ± 11.04 and 61.74 ± 7.51, respectively. March 2020 recorded the highest mean CSTI value (70.14 ± 4.04), while in September 2020, the lowest mean value (58.03 ± 6.22) was obtained. Based on CTSI values, the lake was eutrophic in both dry and wet seasons albeit with differences in the values. The eutrophic state of the lake is possibly attributed to nutrients inflow into the lake via runoff and drainage from farmlands. The negative value of TSI-Chl-a–TSI-TP deviation pointed out that the lake is not phosphorus limited, while the positive TSI-Chl-a–TSI-SD mean deviation value revealed the effect of Chl-a and TP on the lake’s transparency. The study recommends the necessity to develop guidelines for the trophic status monitoring of Lake Bunyonyi since results suggest the deteriorating lake condition.